Alternating hot and cold water immersion for athlete recovery: a review - Cochrane, D. J. (Physical Therapy in Sport, 2004)
Objectives: The aim of this review was to investigate whether alternating hot-cold water treatment is a legitimate training tool for enhancing athlete recovery. A number of mechanisms are discussed to justify its merits and future research directions are reported. Alternating hot-cold water treatment has been used in the clinical setting to assist in acute sporting injuries and rehabilitation purposes. However, there is overwhelming anecdotal evidence for it's inclusion as a method for post exercise recovery. Many coaches, athletes and trainers are using alternating hot-cold water treatment as a means for post exercise recovery. Design: A literature search was performed using SportDiscus, Medline and Web of Science using the key words recovery, muscle fatigue, cryotherapy, thermotherapy, hydrotherapy, contrast water immersion and training. Results: The physiologic effects of hot-cold water contrast baths for injury treatment have been well documented, but its physiological rationale for enhancing recovery is less known. Most experimental evidence suggests that hot-cold water immersion helps to reduce injury in the acute stages of injury, through vasodilation and vasoconstriction thereby stimulating blood flow thus reducing swelling. This shunting action of the blood caused by vasodilation and vasoconstriction may be one of the mechanisms to removing metabolites, repairing the exercised muscle and slowing the metabolic process down. Conclusion: To date there are very few studies that have focussed on the effectiveness of hot-cold water immersion for post exercise treatment. More research is needed before conclusions can be drawn on whether alternating hot-cold water immersion improves recuperation and influences the physiological changes that characterises post exercise recovery.